Money Demand in Indonesia: Does Economic Uncertainty Matter? - Kurniawan, Mahrus Lutfi Adi; A'yun, Indanazulfa Qurrota; Perwithosuci, Winny (Jurnal Ekonomi & Studi Pembangunan, 2022)
Since the global financial crisis of 2008, there has been a rise in economic uncertainty and money demand research. The money demand is vital in monetary policy, which has implications for the regional economy. This study aims to analyse the money demand in Indonesia in the middle of global economic uncertainty, as well as the contribution of the study, which includes the economic and monetary policy uncertainty in a separate model for an enhanced money demand function. The study used a structural vector autoregressive (SVAR) approach. The results indicate that monetary demand is negatively affected by economic uncertainty. With the development of the financial sector, the impact of economic uncertainty and the unpredictability of US monetary policy drives people to be more cautious, resulting in a movement of "wealth" to other instruments. The current study implies that the monetary policy in the form of interest rates as the response to the global condition should consider monetary aggregates in terms of money demand as a precautionary measure to maintain money demand. The study revealed that stable money demand suggests inflation targeting as a monetary policy that can enhance monetary policy in the face of rising economic uncertainty.